2003
DOI: 10.1056/nejmoa022206
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Brief Observation Period for Patients with Cocaine-Associated Chest Pain

Abstract: Patients with cocaine-associated chest pain who do not have evidence of ischemia or cardiovascular complications over a 9-to-12-hour period in a chest-pain observation unit have a very low risk of death or myocardial infarction during the 30 days after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(66 citation statements)
references
References 25 publications
2
61
2
1
Order By: Relevance
“…The association of cocaine use with acute aortic dissection and the causal relationship of cocaine use with acute aortic dissection are not well defined (4,10,14). Several case reports of aortic dissection have been reported (15)(16)(17)(18)(19), but the article by Hsue et al (20) was the only study that clearly linked cocaine use and aortic dissection (20).…”
Section: Previous Studiesmentioning
confidence: 99%
“…The association of cocaine use with acute aortic dissection and the causal relationship of cocaine use with acute aortic dissection are not well defined (4,10,14). Several case reports of aortic dissection have been reported (15)(16)(17)(18)(19), but the article by Hsue et al (20) was the only study that clearly linked cocaine use and aortic dissection (20).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Cocaine causes tachycardia, and CTA images are dependent on heart rate. However, most patients in this study and prior studies of patients with cocaine-associated chest pain are not tachycardic [7,8,10,59]. There are some patients with tachycardia after cocaine use who may not be candidates for coronary CTA because most protocols for noncocaine-using patients require administration of betaadrenergic blockers for heart rate control, and these agents should be avoided in the setting of cocaine [41,50].…”
Section: Limitationsmentioning
confidence: 85%
“…Efforts to risk-stratify patients with cocaine-associated chest pain early in the ED course have been unsuccessful [7,[9][10][11]. Mittleman et al demonstrated that the greatest risk of AMI is within 60 minutes following cocaine use [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous acute medical problems have been associated with cocaine abuse, including cardiac dysrhythmias [2][3][4][5][6][7]. Although the etiology of cocaine-associated dysrhythmias is complex and not fully understood, lethal ventricular dysrhythmias are a theorized cause of sudden death associated with cocaine use [8].…”
Section: Introductionmentioning
confidence: 99%